Pengaruh Dukungan Sosial terhadap tingkat Stres dalam Penyusunan Tugas Akhir Skripsi - Daawi, Muhammad Mujib; Nisa, Walda Isna (Psikodinamika: Jurnal Literasi Psikologi, 2021)
Often times, the thesis writing stage is seen as a phase full of obstacles that can cause stress. Social support is one of the factors that can reduce pressure when individuals experience a problem. The purpose of this study was to determine the effect of social support on stress levels in the preparation of thesis final project. The number of research subjects was 40 student subjects who were working on their thesis. Retrieving data using a scale and interviews. The Social Support Scale with reliability (α) = 0.90 and the Stress scale with the reliability scale (α) = 0.89. The analysis showed that there was no influence of social support on stress levels in preparation of the thesis (B=-0.30; p> 0.05). The results of the interview showed that social support had no effect on the stress experienced by students in working on their thesis, because the social support that was obtained did not match their needs. So that individuals who will provide assistance need to determine the needs and types of social support needed.